Numerical investigation and thermal transport features of magnetic hybrid nanoparticles flow over a poignant tiny needle subject to Joule heating and slip boundary conditions - Iqbal, Zahoor; Priya, S.; Abdul Hakeem, A. K.; Selmi, Ridha; Alsawi, Abdulrahman; Nour, Manasik M.; Hajjej, Fahima; Ameer Ahammad, N.; Ahmed Alyami, Maryam; Yousef, El Sayed (Modern Physics Letters B, 2024)
The primary purpose of this study is to provide more information on the stable and incompressible stream of a hybrid nanofluid over a poignant tiny needle in two dimensions under slip boundary conditions. In the hybrid nanofluid flow, Al2O3 and Fe3O4 are nanoparticles, water and ethylene glycol (50:50) are considered as the base fluids. Furthermore, the impacts of Joule heating and inclined magnetic fields are considered. The PDE’s governing equations are converted into ODEs by using similarity transformations and solved by a numerical technique based on Runge–Kutta fourth-order method. The results illustrate that the crucial parameters such as the magnetic parameter, Eckert number, nanoparticles of solid volume fractions, inclined angle parameter, and Prandtl numbers significantly affect the momentum and thermal profiles. The heat transfer rate and skin friction factors are used to calculate the numerical values of various parameters, which are displayed in a table. These analyses manifest that raising the magnetic parameter results in a decrease in the hybrid nanofluid velocity under slip and no-slip circumstances. The Nusselt number has also grown as a result of the volumetric fractions of nanoparticles and the intensification of the angle parameter. This analysis might include areas such as microfluidics, biomedical devices, heat exchangers, and other engineering applications where precise control over fluid behavior and temperature distribution is important.